Making connections that work a biblical guide to building and maintaining godly relationships - Fergusson, Robert (Smithfield, NSW Prelude, 2003)
Includes bibliographical references.
Donated by Hillsong International Leadership College
Keywords: Interpersonal relations -- Religious aspects -- Christianity; Social networks -- biblical teaching